A "copa das copas": o uso político-ideológico do futebol em propagandas governamentais - Sá, Ariane Boaventura da Silva (2016)
In 2014, Brazil hosted the FIFA (Fédération Internationale de Football Association) World Cup. Due of this, the Federal Government launched a set of advertisements about the mega event in the media, especially in open television, perpetuating the historical practice of using football with political and ideological purposes in the country. Thus, the aim of this research is to check how was the political and ideological usage of football in government advertisements related to the World Cup 2014.Among the set of the advertisements launched, four pieces were selected and analyzed into four different categories:1)Policy Platform; 2) Nationalism; 3) Acceptance of the Cup; 4) For the analyzes were based on the concepts of Text Analysis and Semiotics, both in verbal and non-verbal elements. To this end, it was used Mikhail Bakhtin's guidelines for verbal texts and Roland Barthes`s and Jacques Durand for the non-verbal texts. Considering the selected ads and the theoretical framework it was identified, in terms of intertextual relations, the attempt to promote politically the Labor Party (PT); Party that sustains the base of the Federal Government nowadays, as well as inroads that could trigger the Party re-election, in 2014, due to it was an election year in Brazil. Thus, there was a need to bloom the exacerbated nationalism feeling through ideological signals such as the Brazilian flag colors, gestures and expression of proud, happiness and unity. Further to this, there was an intention to promote the World Cup acceptance by itself, once one year before the event the population was unsatisfied with the event execution. At last, it was identified the usage of Football in order to avoid racism, especially during the event. Therefore, it can be conclude that the political and ideological usage of football took place in the construction of the set of government advertisements "Cup of the Cups" for the following reasons: an attempt to exacerbate the sense of nationalism; promote the main party of the government coalition; create expectations conducive to the realization of the mega event; and ultimately contribute to the fight against racism.